2022
DOI: 10.3389/fphys.2022.874172
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Immune-Related and Antioxidant Genes Expression, and Gut Bacterial Abundance of Pacific White Leg Shrimp, Litopenaeus vannamei, Dietary Supplemented With Natural Astaxanthin

Abstract: The current study examines the effect of dietary supplementation of ethanolic extract of Arthrospira platensis NIOF17/003, which is mainly natural astaxanthins (97.50%), on the growth performance, feed utilization, bacterial abundance, and immune-related and antioxidant gene expressions of the Pacific white leg shrimp, Litopenaeus vannamei. A total of 360 healthy L. vannamei postlarvae (0.19 ± 0.003 g) were divided into four groups (0, 2, 4, and 6 g natural astaxanthins/kg diet) each in three replicates, at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 87 publications
3
17
0
Order By: Relevance
“…The current work reported that, compared to SWP 0 , the THB and TVC counts were significantly ( p > 0.05) decreased with the increase in the inclusion levels of polysaccharides (SWP 1 , SWP 2 , and SWP 3 ). These results are in agreement with those reported in the study by Mansour et al [ 87 ] who found that the increasing levels of astaxanthin, extracted from the cyanobacterium strain, Arthrospira platensis NIOF17/003, in L. vannamei diet significantly ( p > 0.05) decreased the counts of THB and TVC. However, the action mechanism of how seaweed-polysaccharide affected the abundance of microbiota is still not clear and requires further studies [ 87 , 101 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The current work reported that, compared to SWP 0 , the THB and TVC counts were significantly ( p > 0.05) decreased with the increase in the inclusion levels of polysaccharides (SWP 1 , SWP 2 , and SWP 3 ). These results are in agreement with those reported in the study by Mansour et al [ 87 ] who found that the increasing levels of astaxanthin, extracted from the cyanobacterium strain, Arthrospira platensis NIOF17/003, in L. vannamei diet significantly ( p > 0.05) decreased the counts of THB and TVC. However, the action mechanism of how seaweed-polysaccharide affected the abundance of microbiota is still not clear and requires further studies [ 87 , 101 ].…”
Section: Discussionsupporting
confidence: 93%
“…Gut microbiota abundance rapidly responds to variations in dietary intake, composition, and components. Therefore, it has a huge impact on the health benefits of all aquatic organisms such as food consumption, digestion, nutrient utilization, absorption, and immunity responses [ 22 , 87 , 100 , 101 ]. At present, the evaluation of disease resistance is important in the aquaculture industry, the blood antioxidant and immune factor activity is a good health status indicator for investigating the immune response and disease resistance in L. vannamei such as white spot syndrome virus (WSSV) [ 49 ] and Vibrio alginolyticus [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seaweeds are marine organisms rich in numerous phytochemical bioactive compounds that can be used for commercial applications [ 9 , 10 , 11 , 12 , 13 , 14 ]. Seaweeds have applications in fuels [ 15 , 16 , 17 ], feed [ 18 , 19 , 20 ], bioremediation [ 21 , 22 , 23 , 24 ], and food products [ 25 , 26 ]. The Egyptian coasts of the Mediterranean [ 27 , 28 , 29 ] and Red Sea [ 30 , 31 ] offer a diverse range of wild seaweed genera that may renew and be harvested all year.…”
Section: Introductionmentioning
confidence: 99%